2016
DOI: 10.18280/ijht.340116
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Thermodynatic Performances of Mg2Sn Compound via First Principle Calculations

Abstract: Thermodynamic performances of Mg2Sn metal compounds were calculated by first principle calculations. This study, based on density functional theory, calculated lattice constants, band structure and elastic constants to detail the thermal stability of Mg2Sn structures, and then focused on the phonon density of states, constant volume and Debye temperature to deal with thermodynamic properties. Additionally, the calculations were compared with available experimental value and previous theoretical data, and a fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Materials having holes are the majority/minority charge carriers, S is positive/negative. 3,33,[37][38][39]44,5133,[37][38][39]44,51 The S for the above said alloys shows the positive values which means that the major carriers are holes and the materials are belongs to p-type semiconductors. 36,[52][53][54][55] Mg 2 Sn shows negative S at 100 K suggests n-type semiconductor.…”
Section: Resultsmentioning
confidence: 96%
“…Materials having holes are the majority/minority charge carriers, S is positive/negative. 3,33,[37][38][39]44,5133,[37][38][39]44,51 The S for the above said alloys shows the positive values which means that the major carriers are holes and the materials are belongs to p-type semiconductors. 36,[52][53][54][55] Mg 2 Sn shows negative S at 100 K suggests n-type semiconductor.…”
Section: Resultsmentioning
confidence: 96%
“…The Mg-Sn phase diagram corresponds to that of a classical two-eutectic congruently melting linecompound system [26]; any deviation from the 2/1 atomic ratio would therefore result in the presence of Sn-or Mg-free metal. The Mg2Sn phases are known to be slightly reactive to oxygen and highly reactive to water; therefore, there might be oxide layer growth at the surface of the particles [26], [27]. Elemental analysis of the Mg-Sn films was carried out through EDS measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Highresolution narrow scans were employed to examine the core level elements, such as Mg 1s, Mg 2p, and Sn 3d, in the Mg-Sn films. The cubic Mg2Sn has an anti-fluorite crystal structure (No.255, space group is Fm3m, and the lattice constant of 0.676 nm), which consists of interpenetrating fcc cubic lattices with Sn 4+ at the origin (0, 0, 0) and Mg 2+ at the ± (1/4, 1/4, 1/4) position [27], [32]. In addition, the coordination number of each Sn ion is 8, while each Mg ion is located in the middle of the Sn 4+ tetrahedral crystal structure [26].…”
Section: Resultsmentioning
confidence: 99%
“…Molecular simulation, based on the first principle [12,13] and as a rapid developing research method, is now widely used, as Stephen W. Watt et al [14] used molecular simulation to research the melting temperature and glass transition temperature of myo-inositol and neo-inositol. The results showed that the glass transition temperature was 217 ℃ and 245 ℃ respectively, and a small change in the molecular structure of the two molecules led to a sharp rise in the melting point.…”
Section: Introductionmentioning
confidence: 99%